Hyperhidrosis treatments in hidradenitis suppurativa: A systematic review. Issue 1 (30th November 2021) - Shih, Terri; Lee, Katrina; Seivright, Justine R.; De, Devea R.; Shi, Vivian Y.; Hsiao, Jennifer L.
Abstract: Hyperhidrosis impairs quality of life (QOL) in hidradenitis suppurativa (HS) patients and may exacerbate HS. However, there is limited literature on whether hyperhidrosis treatments improve HS disease. To systematically review literature on efficacy and tolerability of hyperhidrosis treatments in HS patients. In May 2021, MEDLINE and EMBASE databases were systematically searched by two reviewers per PRISMA guidelines for articles on hyperhidrosis and HS. Sixteen articles met inclusion criteria (2 randomized controlled trials [RCTs], one case–control study, three cross‐sectional studies, 10 case‐studies/series), encompassing 252 HS patients across studies. They examined botulinum toxin A (BTX‐A) ( n  = 6) and B (BTX‐B) ( n  = 1), suction‐curettage ( n  = 1), diode laser ( n  = 1), and microwave‐based energy device (MED) ( n  = 3). Overall, BTX treatments improve HS severity, QOL, hyperhidrosis, and were well‐tolerated. Suction‐curettage did not improve disease. One HS patient tolerated diode laser well, with improvement in sweating and HS. One RCT studying MED was discontinued due to adverse events. Two studies reported MED‐induced HS. BTX was overall helpful in HS patients, including in patients without concomitant hyperhidrosis. However, more prospective studies are needed to examine its utility in HS. There is potential harm of MEDs in HS. Most studies examining hyperhidrosis treatments in HS patients are low level of evidence. Larger RCTs should examine the efficacy and tolerability of hyperhidrosis treatments in HS.